Berryman's Sickness Unto Death. (March 2018) - Mouw, Alex
In his copy of Søren Kierkegaard's The Sickness Unto Death, John Berryman inserted a handwritten note entitled "Sense of Guilt, " which ends in an existential prayer: "I tremble — I am afraid — Jesus, Son of God, help me." Twenty years later, Berryman published one of his most substantial collections of poetry: 77 Dream Songs . And though the Dream Songs were published long after Berryman left his anxious comments in The Sickness Unto Death, I argue that they enact a struggle with the Christian concepts of despair and the self as Berryman learned them from Kierkegaard.